Fermi surface and effective masses in photoemission response of the (Ba1-x K x )Fe2As2 superconductor - Derondeau, Gerald; Bisti, Federico; Kobayashi, Masaki; Braun, Jürgen; Ebert, Hubert; Rogalev, Victor A; Shi, Ming; Schmitt, Thorsten; Ma, Junzhang; Ding, Hong; Strocov, Vladimir N; Minár, Ján (Scientific reports, 2017)
The angle-resolved photoemission spectra of the superconductor (Ba1-x K x )Fe2As2 have been investigated accounting coherently for spin-orbit coupling, disorder and electron correlation effects in the valence bands combined with final state, matrix element and surface effects. Our results explain the previously obscured origins of all salient features of the ARPES response of this paradigm pnictide compound and reveal the origin of the Lifshitz transition. Comparison of calculated ARPES spectra with the underlying DMFT band structure shows an important impact of final state effects, which result for three-dimensional states in a deviation of the ARPES spectra from the true spectral function. In particular, the apparent effective mass enhancement seen in the ARPES response is not an entirely intrinsic property of the quasiparticle valence bands but may have a significant extrinsic contribution from the photoemission process and thus differ from its true value. Because this effect is more pronounced for low photoexcitation energies, soft-X-ray ARPES delivers more accurate values of the mass enhancement due to a sharp definition of the 3D electron momentum. To demonstrate this effect in addition to the theoretical study, we show here new state of the art soft-X-ray and polarisation dependent ARPES measurments.